Effectiveness of parenteral nutrition order form in neonates - Aeimcharnbanchong, Kanokwan; Luecha, Orawin (Journal of Medicine and Health Sciences, 2023)
Parenteral nutrition (PN) is essential for the growth of pre-term and very low birth weight neonates. However, PN is a risky intravenous feeding procedure with many components. Moreover, PN prescribing requires specific knowledge of the person who prescribes the order. Therefore, there is a high possibility of PN prescribing errors which can affect neonates and working at the Neonatal Intensive Care Unit (NICU) of Panyananthaphikkhu Chonprathan Medical Center (PCMC), there have been many PN prescribing errors. Therefore, This study prepare the PN Order Form with an objective to measure the effectiveness of using the form, which can be measured by the following: 1) PN prescribing errors; 2) day of life that the weight of the neonate returns to birth weight; and 3) abnormal results of laboratory tests before and after the use of the form. The quasi-experimental historical control group study was performed to compare the group before and the group after using the form (control group and intervention group) in a single-center NICU of PCMC from December 2020 to November 2022. It was found that there were 166 orders with errors in 229 orders or 72.5% of the control group. For the intervention group, there were only 15 orders with errors out of 236 orders or 6.4%. The errors in the intervention group were reduced and statistically significant. It was also found that the weight of the neonate returned to birth weight in 11.8 days for the control group, compared with 7.6 days for the intervention group. The weight of the intervention group returned to birth weight statistically and significantly faster. According to the laboratory tests, 17.7% of the control group had hyponatremia and compared to 2.6% of the intervention group. The numbers of hyponatremia observed in the intervention group were statistically and significantly reduced. Therefore, the PN Order Form can statistically and significantly reduce PN prescribing errors, to help the weight of the neonates return to birth weight faster and reduced the hyponatremia of the neonates.